Patient Uncertainty Questionnaire-Rheumatology (PUQ-R): development and validation of a new patient-reported outcome instrument for systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) in a mixed methods study. Issue 1 (December 2016) - Cleanthous, Sophie; Isenberg, David; Newman, Stanton; Cano, Stefan
Abstract Background An in-depth qualitative exploration of uncertainty in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) led to the development of a five-domain conceptual framework of patient uncertainty in these two conditions. The purpose of this study was to develop and evaluate a new patient-reported outcome (PRO) instrument for patient uncertainty in SLE and RA on the basis of this empirically developed conceptual framework. Methods Cognitive debriefing interviews were conducted to pre-test the initial items generated on the basis of the preliminary qualitative exploration of patient uncertainty in SLE and RA. Two separate field tests were conducted in five hospital sites to evaluate the measurement properties of the new instrument; the first to identify and form scales, and the second to assess measurement properties of the final version in an independent sample. Psychometric evaluation was conducted in line with the Rasch Measurement Theory (RMT), examining the extent to which sample to scale targeting was satisfactory, measurement scales were constructed effectively and the sample was measured successfully. Traditional psychometric techniques were also used to provide complementary analyses best understood by clinicians. Results Pre-testing supported the relevance, acceptability and comprehensibility of the initial items. Findings indicated that the Patient Uncertainty Questionnaire for Rheumatology PUQ-R instrument fulfilled the expectations of RMT to a large extent (including person separation index 0.73 – 0.91). The PUQ-R comprises 49 items across five scales; symptoms and flares (14 items), medication (11 items), trust in doctor (8 items), self-management (6 items) and impact (10 items) which further displayed excellent measurement properties as assessed against the traditional psychometric criteria (including Cronbach's alpha 0.82 – 0.93). Conclusion The PUQ-R has been developed and evaluated specifically for patients with SLE and RA. By quantifying uncertainty, the PUQ-R has the potential to support evidence-based management programmes and research.